Arabidopsis thaliana CYCLIC NUCLEOTIDE‐GATED CHANNEL2 mediates extracellular ATP signal transduction in root epidermis. Issue 2 (20th February 2022) - Wang, Limin; Ning, Youzheng; Sun, Jian; Wilkins, Katie A.; Matthus, Elsa; McNelly, Rose E.; Dark, Adeeba; Rubio, Lourdes; Moeder, Wolfgang; Yoshioka, Keiko; Véry, Anne‐Aliénor; Stacey, Gary; et al.
Summary: Damage can be signalled by extracellular ATP (eATP) using plasma membrane (PM) receptors to effect cytosolic free calcium ion ([Ca 2+ ]cyt ) increase as a second messenger. The downstream PM Ca 2+ channels remain enigmatic. Here, the Arabidopsis thaliana Ca 2+ channel subunit CYCLIC NUCLEOTIDE‐GATED CHANNEL2 (CNGC2) was identified as a critical component linking eATP receptors to downstream [Ca 2+ ]cyt signalling in roots. Extracellular ATP‐induced changes in single epidermal cell PM voltage and conductance were measured electrophysiologically, changes in root [Ca 2+ ]cyt were measured with aequorin, and root transcriptional changes were determined by quantitative real‐time PCR. Two cngc2 loss‐of‐function mutants were used: cngc2‐3 and defence not death1 (which expresses cytosolic aequorin). Extracellular ATP‐induced transient depolarization of Arabidopsis root elongation zone epidermal PM voltage was Ca 2+ dependent, requiring CNGC2 but not CNGC4 (its channel co‐subunit in immunity signalling). Activation of PM Ca 2+ influx currents also required CNGC2. The eATP‐induced [Ca 2+ ]cyt increase and transcriptional response in cngc2 roots were significantly impaired. CYCLIC NUCLEOTIDE‐GATED CHANNEL2 is required for eATP‐induced epidermal Ca 2+ influx, causing depolarization leading to [Ca 2+ ]cyt increase and damage‐related transcriptional response.